PRAKTEK PEMBANGUNAN KESEHATAN MASYARAKAT (PPKM) PENYULUHAN DAN PENINGKATAN PERILAKU HIDUP BERSIH SEHAT (PHBS) DI SDN. MOJOGENENG KEC. JATIREJO KAB. MOJOKERTO - Acivrida Mega Charisma; Adita Laila Rachma; Erisa Listiany; Nabila Farah Fernita; Nita Puspita; Ucik Musdalifah; Winda Sefti Febriari (Journal of Science and Social Development, 2019)
Students of Mojogeneng elementary school in Mojokerto has not awareness of healthy hygiene behavior. even though it is very important. if not considered will cause disease, one of them is a worm disease. This activity aims to invite students to accustom healthy hygiene behavior in theory and practice. moreover, studying entrepreneurship, growing rosella plants, studying together, and hold a contest too. The result of this activity is the student is very enthusiastic and always participate in every activity. So that, they realize the importance of healthy hygiene behavior, more active, and creative.